Annual Plan 1995-96 Review and Outline Volume - I Government of Manipur - Planning Commission (Planning Commission, 1995)
Nine-tenth of features total area of 22,327 sq. kms. consists of hills and only one-tenth is valley. The State does not have any waterways or effective railway system to link with other parts of the country. The nearest rail heads are at Dimapur and Jiri bam, 215 and 222 kms. away respectively of the two National Highways which connect Imphal with Dimapur and Silchar, the latter is of Class-IX standard end as such cannot be used by heavy vehicles during the rainy season.
Planning Department Government of Manipur